Damping characteristics of single-layer aluminum alloy reticulated spatial structures based on improved modal parameter identification method. (July 2021) - Guo, Xiaonong; Zhang, Jindong; Zhu, Shaojun; Luo, Xiaoqun; Xu, Hongjun
Abstract: An improved identification method is proposed for the modal parameter identification of multi-modal vibration attenuation signals based on the analytical mode decomposition and the particle swarm optimization. Through examples of analog signals, it is proved that the proposed method can identify modal parameters under a strong colored noise environment. Field tests were carried out on four in-service aluminum alloy reticulated structures to obtain the acceleration response of the structures. The improved identification method proposed in this paper is used to identify the modal parameters of each acceleration response curve, based on which the damping characteristics of the aluminum alloy reticulated structures are analyzed. The results show that the damping characteristics of such structures obey a three-stage change rule, with the increase of the acceleration amplitude. In addition, a practical calculation method of the damping ratios of aluminum alloy reticulated structures is proposed on the basis of the experimental results. Highlights: An improved modal parameter identification method is proposed based on AMD and PSO. The proposed modal parameter identification method is effective in dealing with signals with colored noise. Damping characteristics of aluminum alloy reticulated spatial structures satisfy a three-stage change rule. Practical calculation method of the damping ratios of aluminum alloy reticulated structures is proposed.